Risk behaviours for HIV infection among travelling Mexican migrants: The Mexico–US border as a contextual risk factor. Issue 1 (2nd January 2017) - Zhang, Xiao; Martinez-Donate, Ana P.; Simon, Norma-Jean E.; Hovell, Melbourne F.; Rangel, Maria Gudelia; Magis-Rodriguez, Carlos; Sipan, Carol L.
ABSTRACT: The Mexico–US border region is a transit point in the trajectory of Mexican migrants travelling to and from the USA and a final destination for domestic migrants from other regions in Mexico. This region also represents a high-risk environment that may increase risk for HIV among migrants and the communities they connect. We conducted a cross-sectional, population-based survey, in Tijuana, Mexico, and compared Mexican migrants with a recent stay on the Mexico–US border region (Border, n  = 553) with migrants arriving at the border from Mexican sending communities (Northbound, n  = 1077). After controlling for demographics and migration history, border migrants were more likely to perceive their risk for HIV infection as high in this region and regard this area as a liberal place for sexual behaviours compared to Northbound migrants reporting on their perceptions of the sending communities ( p  < .05). Male border migrants were more likely to engage in sex, and have unprotected sex, with female sex workers during their recent stay on the border compared to other contexts (rate ratio = 3.0 and 6.6, respectively, p  < .05). Binational and intensified interventions targeting Mexican migrants should be deployed in the Mexican border region to address migration related HIV transmission in Mexico and the USA.